Respuesta :
-----------------
0.04m² - n²
(0.2m)² - n²
(0.2m + n)(0.2m - n)
-----------------
0.04m² - n²
(0.2m)² - n²
(0.2m + n)(0.2m - n)
-----------------
Answer:
[tex]0.04m^2-n^2=(0.2m-n)(0.2m+n)[/tex]
Step-by-step explanation:
We have to factorize the given expression i.e [tex]0.04m^2-n^2[/tex]
According to the identity of [tex]a^2-b^2[/tex]
[tex]a^2-b^2=(a-b)(a+b)[/tex]
Given expression is
[tex]0.04m^2-n^2=(0.2m)^2-n^2\\\\a=0.2m, b=n\\\\implies\\(0.2m-n)(0.2m+n)[/tex]
Hence, [tex]0.04m^2-n^2=(0.2m-n)(0.2m+n)[/tex]